Tables of Volume for Individual Trees in Eucalyptus globulus ssp. globulus in Southern Uruguay - Moras, Guillermo; Vallejos-Barra, Oscar Santiago (Agrociencia Uruguay, 2013)
We developed individual tables for total and commercial volume for Eucalyptus globulus ssp. globulus in commercial planta-tions located in southern Uruguay, in 13 farms between six and 11 years old, with a density between 1111 and 1667 trees per hectare. to 266 randomly selected trees using a parallel-arm calliper . We felled the trees and recorded height with a tape. We measured the diameter every meter long and calculated the volume with the formula of Smalian; we obtained the tree volume by adding the volumes of the sections. We determined the variables better correlated with the total and commercial volumes, and used these variables to build mathematical models. We selected these models based on the highest adjusted R2 and the lowest MSE (Mean Square Error of Prediction). We determined the total volume with bark [ Ln (Total volume ) = -9.75 + 0.93 * Ln ( DAP2 * h total) + ε] with adjusted R2 of 0.98 and 0.02 MSE. We estimated the commercial volume with bark by [ Ln (commercial volume) = -8.22 + 0.77 * Ln (DAP2 * commercial h) + ε] with adjusted R2 of 0.95 and 0.06 MSE. For each of the farms we selected the local functions with greater significance for both the total and the commercial volume.